The effect of Crocus sativus L. (saffron) herbal tea on happiness in postmenopausal women: a randomized controlled trial - Hamed Delam; Zahra Keshtkaran; Nasrin Shokrpour; Ahmadreza Eidi; Mohammad-Rafi Bazrafshan (BMC, 2023)
Abstract Background Evidence suggests that menopause can be associated with a variety of negative psychological changes such as depression and anxiety, and improving the mental health status of women during menopause is one of the important priorities and challenges of the health system. The aim of this study was to determine the effect of saffron (Crocus sativus L., Iridaceae) herbal tea on happiness in postmenopausal women. Methods In this randomized clinical trial which was conducted in 2021, 72 postmenopausal women were enrolled and divided into intervention and control groups. The randomization blocks method was used for random allocation, and the Oxford Happiness Questionnaire was utilized to measure the scores. The intervention included the use of 30 mg of dried stigmas of the saffron plant, which was boiled once (in the morning, in 300 ml of boiling water for 10-15 min) and consumed with white rock candy as one cup of saffron tea daily. To compare the trend of changes and after removing the effect of other variables, generalized estimating equation (GEE) was used. Results There was no significant difference between the intervention and control groups in any of the quantitative and qualitative characteristics (p > 0.05). The results of paired samples t-test showed that the happiness mean score in the intervention group increased significantly (p < 0.001) from 42.93 ± 8.54 to 61.58 ± 8.24, while in the control group, there was no significant difference between the happiness mean score at the beginning and end of the study (p = 0.861). Also, after applying the treatment program in the intervention group, there was a significant difference between the two groups in terms of the happiness mean scores (p < 0.001). Conclusion Saffron herbal tea had a positive effect on reducing depression and increasing the happiness score; thus, it is recommended that it should be used as a complementary treatment in consultation with the treating physician. Trial registration The present study was registered with the code of IRCT20210403050818N1 (Registration date: 09/04/2021) in the Iranian Registry of Clinical Trials. It was also approved by the Ethics Committee of Larestan University of Medical Sciences (Approval ID: IR.LARUMS.REC.1399.017).